Product lifecycle management through innovative and competitive business environment - Valentina Gecevska; Paolo Chiabert; Zoran Anisic; Franco Lombardi; Franc Cus (Journal of Industrial Engineering and Management (JIEM), 2010)
Product Lifecycle Management (PLM) is the process of managing the whole life cycle of a product starting from generating an idea, concept description, business analyzes, product design and solution architecture and technical implementation, to the successful entrance to the market, service, maintenance and product improvement. At present, a wide range of stakeholders including consumers, regulators, shareholders and public bodies are demanding that companies address product management through all life cycle in a more comprehensive and sustainable way. However, even if a company actually wishes innovate its processes for improving the way to account for project management, it will face relevant difficulties to deal with different guidelines, tools and methods currently addressing the matter from various points of view. The purpose of this paper is to review literature on PLM from an operational point of view with the objective to help companies to answer to the main market needs.
Keywords: 650; product lifecycle management; business process; competitiveness